ANALISIS POTENSI EKONOMI DAN RELEVANSI SYARIAH DALAM BISNIS LAHAN MAKAM PREMIUM - Nurul Kharisma; Niswatun Hasanah (Universitas KH. Mukhtar Syafaat, 2026)
This study aims to analyze the compliance of Al-Azhar Memorial Garden's business practices in light of the MUI Fatwa Number 09 of 2014 concerning the Purchase and Sale of Graveyards, as well as its implications for socio-economic distributive justice. The research method employed is descriptive qualitative with a juridical-normative approach and an Islamic socio-economic approach. Data were collected through the documentation study of fatwa texts, waqf regulations, and publication data regarding the management of the research object. The results indicate that in terms of physical worship, Al-Azhar Memorial Garden has strived to comply with sharia provisions and the MUI Fatwa by maintaining the simplicity of the grave structure (grass lawns without grand monuments). However, from the perspective of muamalah and distributive justice, this high-tariff commercialization scheme potentially violates the principle of Hifzh al-Mal due to its proximity to israf (extravagance) and creates spatial exclusivity amidst the urban land emergency. This study recommends the optimization of productive waqf instruments as a cross-subsidy solution to achieve more inclusive and socially just burial access. Keywords: Cemetery Commercialization, MUI Fatwa, Maqashid Shariah